1999
DOI: 10.1038/sj.leu.2401578
|View full text |Cite
|
Sign up to set email alerts
|

Frequent co-expression of the HOXA9 and MEIS1 homeobox genes in human myeloid leukemias

Abstract: There is increasing evidence that HOX homeobox genes play a role in leukemogenesis. Recent studies have demonstrated that enforced co-expression of HOXA9 and MEIS1 in murine marrow leads to rapid development of myeloid leukemia, and that these proteins exhibit cooperative DNA binding. However, it is unclear whether co-activation of HOXA9 and MEIS genes is a common occurrence in human leukemias. We surveyed expression of HOXA9 and MEIS1 in 24 leukemic cell lines and 80 patient samples, using RNase protection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(174 citation statements)
references
References 33 publications
(32 reference statements)
7
165
0
2
Order By: Relevance
“…The unequivocal role of Hox genes in the pathogenesis of acute leukemia A central role for HOX genes in hematological malignancies is supported by the frequently observed elevation of HOX and MEIS1 gene expression in AML patient samples (Golub et al, 1999;Kawagoe et al, 1999;Lawrence et al, 1999;Afonja et al, 2000;Drabkin et al, 2002). Indeed, HOXA9 is the single most highly correlated gene (out of 6817) for poor prognosis in AML (Golub et al, 1999).…”
Section: Deficiencies Of Hox Regulators Demonstrate a Role For Hox Gementioning
confidence: 98%
“…The unequivocal role of Hox genes in the pathogenesis of acute leukemia A central role for HOX genes in hematological malignancies is supported by the frequently observed elevation of HOX and MEIS1 gene expression in AML patient samples (Golub et al, 1999;Kawagoe et al, 1999;Lawrence et al, 1999;Afonja et al, 2000;Drabkin et al, 2002). Indeed, HOXA9 is the single most highly correlated gene (out of 6817) for poor prognosis in AML (Golub et al, 1999).…”
Section: Deficiencies Of Hox Regulators Demonstrate a Role For Hox Gementioning
confidence: 98%
“…[50][51][52][53][54] Several LAAs have also been implicated in the multi-step leukemic transformation of hematopoietic progenitor cells, for example, ETO/MTG8, 55 hTERT 56 and the homeobox protein HOXA9. 57 The LAA WT1 may contribute to leukemogenesis by interfering with normal hematopoietic progenitor cell differentiation, which is considered as one of the first critical steps in the leukemic transformation of these cells. 16 In a transgenic mouse model, Nishida et al 50 also demonstrated the capacity of WT1 to induce leukemia in collaboration with the t(8;21) fusion protein AML1-ETO.…”
Section: Leukemogenesismentioning
confidence: 99%
“…HOXA9 is the most frequent partner in a fusion oncoprotein with Nup98 (Nup98-HOXA9), resulting from the chromosomal translocation t(7;11)(p15;p15) observed in human leukemia (26 -28). HOXA9 is also known to interact with myeloid ecotropic viral integration site 1 homologue (MEIS1), a member of the three -amino acid loop extension subclass of homeodomaincontaining proteins (29). The MEIS1-HOXA9 interaction has been reported to rapidly accelerate leukemogenesis in mice (30 -32), making these proteins and their interaction a potential therapeutic target for further evaluation.…”
Section: Introductionmentioning
confidence: 99%